Revisiting the Failure of Turkiye’s European Union (EU) Accession Process: Islamophobia and Civilizational Discourse in Europe - Ibrahim, Muhammad Khalis; Rosli, Nurhidayu; Daniels, Timothy P. (Journal of Al-Tamaddun, 2025)
Since being declared eligible for European Union (EU) membership in 1999, Turkiye has undertaken numerous reforms toward accession. Despite meeting several criteria, its accession negotiation has stalled. Existing analyses typically adopt an institutional lens, arguing that the country fails to meet EU benchmarks. Rather than focusing on institutional explanations, this article aims to revisit the failure of Turkiye’s EU accession process through the lens of civilizational discourse in Europe. Methodologically, it employs Critical Discourse Analysis approach by examining statements from several key European political elites and religious leaders, as well as official EU reports. It examines how cultural and religious narratives were shaped in the context of the rejection of Turkiye’s EU membership. This article argues that civilizational discourse has been a prominent lens through which Turkiye has been perceived in the sense of EU accession and European public opinion as a whole. Europeans’ rejection of Turkiye is grounded in the perception of “non-Europeanness” and its incompatibility with Europe’s cultural and religious traditions. While Turkiye’s institutional backsliding has contributed to the accession process being stalled, identity factors remain a persistent barrier. Overall, this study revisits Turkiye’s failed bid to join the EU from a civilizational perspective; the often-overlooked dimension in examining the failure of the accession process. It highlights the need to recognize civilizational Islamophobia as a critical, yet under-analyzed, determinant in the context of EU enlargement policy and broader relations between Europe and Muslims.